3D printing implementation in food industry - Zhylinskaya, Alena; Srivastava, Mohit; Martínez, Felipe; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
3D printing technology is evolving rapidly and offers opportunities that can compete with traditional manufacturing in various industries. Nevertheless, the level of penetration of 3D printing in the food sector is still in the emerging stage. The aim of the paper is to analyze current trends in the 3D food printing and potential applications that can modify traditional business models. The theoretical part deals with existing applications and constraints of additive manufacturing, safety concerns and regulations in 3D food industry. Furthermore, survey questionnaire and semi-structured interviews are analyzed to gather holistic perspective on 3D food development. Finally, several frameworks are used to determine additional value for customer created with this new technology and propose business model innovation.
Vedoucí práce: Mohit Srivastava
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses